2016
DOI: 10.1016/j.aorn.2016.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Perioperative Nurse in Improving Surgical Patients' Clinical Outcomes and Satisfaction: Beyond Medication

Abstract: For the perioperative nurse, the management of postsurgical pain includes various responsibilities, such as performing postsurgical pain assessments as an essential first step, facilitating recovery from surgery, and maximizing patient satisfaction during the postsurgical period. In addition, nurses are responsible for providing patient education regarding pain management, the quality of which may strongly influence patient satisfaction. External and internal challenges exist in perioperative care processes, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 40 publications
(101 reference statements)
1
9
0
14
Order By: Relevance
“…The most reported AE was the presence of pain, followed by postoperative complications (bleeding and wound infection). This is similar to national ( 21 , 37 ) and international ( 38 ) studies and suggest that efficient measures should be taken and safe practices applied ( 12 ) . It is important to note that most AE, such as pain, can be prevented or eliminated if detected early.…”
Section: Discussionsupporting
confidence: 81%
“…The most reported AE was the presence of pain, followed by postoperative complications (bleeding and wound infection). This is similar to national ( 21 , 37 ) and international ( 38 ) studies and suggest that efficient measures should be taken and safe practices applied ( 12 ) . It is important to note that most AE, such as pain, can be prevented or eliminated if detected early.…”
Section: Discussionsupporting
confidence: 81%
“…Empirical evidence has shown that there is need to relieve POP within a reasonable time frame because of its negative effects on clinical outcomes (Bruckenthal & Simpson, 2016; Francis & Fitzpatrick, 2013). Inadequately controlled pain negatively affects quality of life, function, and functional recovery (Kehlet, Jensen, & Woolf, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences are organized into three broad categories related to the patient, employees, and organizational outcomes. Consequences related to patients include optimal patient safety, optimal surgical outcomes, and patient satisfaction . Consequences related to employees are associated with high employee satisfaction .…”
Section: Defining Characteristicsmentioning
confidence: 99%
“…Consequences related to employees are associated with high employee satisfaction . Organizational consequences include high net revenue and a greater likelihood of meeting or exceeding national surgical outcomes, measures, and standards …”
Section: Defining Characteristicsmentioning
confidence: 99%